Individual Differences in Statistical Learning Predict Children's Comprehension of Syntax. Issue 1 (28th October 2015) - Kidd, Evan; Arciuli, Joanne
Abstract : Variability in children's language acquisition is likely due to a number of cognitive and social variables. The current study investigated whether individual differences in statistical learning (SL), which has been implicated in language acquisition, independently predicted 6‐ to 8‐year‐old's comprehension of syntax. Sixty‐eight ( N  =   68) English‐speaking children completed a test of comprehension of four syntactic structures, a test of SL utilizing nonlinguistic visual stimuli, and several additional control measures. The results revealed that SL independently predicted comprehension of two syntactic structures that show considerable variability in this age range: passives and object relative clauses. These data suggest that individual differences in children's capacity for SL are associated with the acquisition of the syntax of natural languages.